Two birds with one stone: a NIR fluorescent probe for mitochondrial protein imaging and its application in photodynamic therapy. Issue 30 (20th July 2021) - Qi, Ya-Lin; Guo, Long; Chen, Li-Li; Yuan, Dan-Dan; Wang, Hai-Rong; Cao, Yu-Yao; Yang, Yu-Shun; Zhu, Hai-Liang
Abstract : A near-infrared fluorescence probe was developed to illuminate the dynamic changes in mitochondrial proteins in live cells under oxidative stress, with excellent temporal and spatial resolution. Abstract : Mitochondrial proteins, most of which are encoded in the nucleus and the rest of which are regulated by the mitochondrial genome, play pivotal roles in essential cellular functions. However, fluorescent probes that can be used for monitoring mitochondrial proteins have not yet been widely developed, thereby severely limiting the exploration of the functions of proteins in mitochondria. Towards this end, here we propose a near-infrared (NIR) fluorescence probe MPP to effectively illuminate the dynamic changes in mitochondrial proteins in live cells under oxidative stress, with excellent temporal and spatial resolution. Of particular importance, MPP extends the study of the pharmacology involved in apoptosis induced by anti-cancer drugs (hydroxycamptothecin (HCPT), epirubicin (Epi) and cyclophosphamide (CPA)) for the first time. Furthermore, employing a protein-activatable strategy, this probe could serve as an excellent phototherapeutic agent in photodynamic therapy (PDT). Finally, in vivo experiments suggest that this versatile probe can be used to image tumors in HeLa tumor-bearing mice for 24 h, which demonstrates that our probe could play a dual role as a robust phototherapeutic and imaging agent.